ORGANIZATIONAL AND ECONOMIC FACTORS OF DEVELOPING LEASING SERVICES, THEIR CLASSIFICATION AND CHARACTERISTICS - Farkhod Abdullaev; Boyjonova Shakarjon (Scholar Express Journals, 2025)
This article provides information on leasing services, revealing the organizational and economic factors of their development, their classification, description, and significance. It highlights proposals for the development of the leasing market, its role in creating economic opportunities for business entities, and expanding its services.
Keywords: Leasing; Services; Leasing market; Business entities